Reconceptualizing Professionalism in the Context of Acupuncture: Setting Standards for Future Acupuncturists, a View from Malaysia - Chee Hee Seng; Linchao Qian; Yun Jin Kim (Mary Ann Liebert, 2022)
Introduction Professionalism and ethical practices in the field of acupuncture is scarcely discussed. Professionalism and medical ethics are important topics in conventional medicine and is the supporting structure gathering human trust and belief in the medical system. Medical professionalism is a set of values, behaviors, and relationships that underpin public trust in doctors.1 It lies at the core of the contract between medical professionals and society,2 and is a stabilizing morally protective force in the society.3 Unprofessional conduct in doctors has been associated with an increased risk of adverse medical outcomes in patients. Thus, to ensure better medical outcomes and well-being of the patient, a uniform system of professional practices must be established within acupuncture. Before this, some research has been done regarding this topic, and our study serves to identify open questions regarding professionalism in acupuncture, including whether biomedical and Traditional Chinese Medicine (TCM) knowledge should be a requirement for professionalism, whether ethics should be considered an aspect of professionalism, differences between interpretations of professionalism, who is responsible for establishing these professional standards, and what we the authors suggest to establish a uniform system of professional values in acupuncture. The objective of this study is to review information related to professionalism in acupuncture and to organize the information in a manner that is presentable and clear to the reader. The review highlights professional standards that needs to be adhered to as well as professional practices in acupuncture, including educational requirements, ethics, professional medical practices, as well as ideal implementation of establishing professionalism. The intended purpose of this article is to support uniform adoption of the recommendations for professional and ethical practices in acupuncture practice. Discussion Limitations: Our study has the following limitations. First, due to the lack of relevant resources about professionalism in acupuncture, we selected relevant sources regarding medical professionalism in conventional medicine as well as surveys in a medical college setting to compare with attributes of professionalism based on requirements set by the Ministry of Health in Malaysia, interviews of TCM practitioners, and two relevant case studies of the professionalization in acupuncture in the United States. The requirements and standards for professionalism in conventional medicine cited in this study are only used as means for comparison. In this study, they are merely representative of professional standards set in the field of biomedicine. Second, we used the databases Google Scholar, Web of Science, and PubMed in conducting the search for relevant articles. Literature in Chinese or other languages have not been browsed. Third, the ethical aspects of professional practice as well as professional research and clinical trial methods will only be briefly discussed as they are not part of this main topic. Finally, ethics in the context of TCM based on ancient texts will not be covered. Our article will mainly focus on available literature regarding professionalism in acupuncture, and we aim to redefine and reconceptualize what we think are necessary attributes of professionalism that are effective in enhancing the professionalism in acupuncture and provide directions for future research. Owing to such limitations, further research in the form of surveys, behavioral inspections, and wider search for available literature in different languages is crucial in conceptualizing a uniform international standard for professionalism in acupuncture. ?Profession can refer to the conventions by which people recognize a given expertise, including knowledge and related skills.?4 Comparing the attributes of professionalism stated by relevant sources, we discovered that only one source mentioned the word principles,5 referring to fundamental principles of professionalism (patient welfare, patient autonomy, and social justice). Commitment to competence,5 continuous improvement,6 lifelong/self-directed learning skills,7 excellence5,6 are similar terms mentioned across different sources. Although there are some similarities, it is evident that even within the field of biomedicine, professionalism is not firmly established with a consensus. However, biomedical standards have found its way into influencing the professionalism of acupuncture.4 Biomedicine has claimed a universally untouchable place in the international medical system and is clearly evidenced by its generally being known as medicine. Supreme Court authorities have deemed it as neither a business nor a trade, and had given it immunity from antitrust suits, and had upheld the exclusivity of its license and of its monopoly and control over practice. Owing to this, biomedicine cannot be referred as the gold standard of professional medical identity for all medical modalities, nor is it the perfect authority to set the gold standards for other medical modalities.4 It is evident that two very different paradigms are at work because acupuncture and biomedicine have mutually exclusive conceptualizations of the body. Owing to the differences in knowledge, theoretical composition, and historical constructs of medical modalities, it is almost impossible for one modality to understand the other, much less define what is professional for the other. That is some experts have recommended to establish a separate standard of professionalism for acupuncture. After reviewing available data, we recommend that professionalism be redefined for acupuncture with unique standards in knowledge, practice, and implementation. The ultimate goal is to bring acupuncture to a professional standard that is acceptable by the biomedical model in knowledge, clinical practice, and efficacy, whereas keeping the TCM theories and philosophies that serve as the guidance for practice. In the following sections, we will discuss several important topics within the profession of acupuncture that are still in debate. Does professionalism include ethics and physician conduct? A survey of 109 students and 83 faculty members of Oman Medical College attained surprising and unexpected results about medical professionalism and identified an unaddressed issue: the current generation may have a different perception of professionalism as their personal values and opinions.8 Although medical students expressed a positive attitude toward professionalism, many in the interview felt that ethical thinking and behavior should not be a part of medical professionalism. However, according to Table 1, most sources regarding medical professionalism (government documents included) place a strong emphasis on the ethical thinking and behavior as a professional attribute. Table 1.